Analisis Supply Chain Operation Reference (SCOR) Models dalam Supply Chain Management Pengiriman Halal Food di Indonesia - Zaimah, Zaimah (Institute of Research and Public Service Universitas Jenderal Soedirman, 2025)
This study aims to analyze the implementation of supply chain management (SCM) in the distribution of halal products in Indonesia through a literature review based on the Halal Supply Chain and SCOR models. Using a descriptive qualitative approach, it examines the application of traceability, segregation, and halal certification across all stages of the supply chain. Although Law No. 33 of 2014 has been implemented, challenges remain in logistics infrastructure, industry awareness, and certification costs, especially for SMEs. The SCOR Model highlights the importance of planning, risk management, and the use of technologies such as blockchain and Internet of Things (IoT). A comparison with Malaysia indicates the need to strengthen infrastructure, regulations, and technology to improve the effectiveness of halal product distribution in Indonesia.